Short Story Buah Limus Murag Ku Angin by Karna Yudibrata: A Study of Immanuel Kant's Philosophy of Norms - Ghoni, Deni Abdul; Koswara, Dedi (Universitas Pendidikan Indonesia, 2024)
This study aims to describe the moral philosophy contained in the Sundanese short story Buah Limus Murag ku Angin by Karna Yudibrata using Immanuel Kant's moral philosophy theory. This research uses a qualitative approach with the document method and literature study. The document method is used to find data sources that will be used, while supporting literature and readings are collected using literature study techniques. The data source in this research is the short story Buah Limus Murag ku Angin by Karna Yudibrata and the data is in the form of morality values contained in it. Then the data is analyzed and described using Immanuel Kant's moral philosophy theory, with the result that in this short story moral philosophy is observed which includes 1) morality towards god not to associate gods, in 2) morality towards the social environment includes morals of responsibility, respect for others, and good neighborliness, and in 3) morality towards oneself the results are related to morals to think positively, not indulge in excessive ego, control emotions, maintain self-esteem and authority, and wisdom in action.